2010
DOI: 10.4161/psb.5.11.12954
|View full text |Cite
|
Sign up to set email alerts
|

RALFs

Abstract: The Discovery of RALFDuring a search for systemins in tobacco, an unrelated peptide factor was discovered that alkalinizes suspension culture medium even more rapidly than systemins. 13 This factor was named RALF, for Rapid ALkalinization Factor. RALF peptide was first purified from tobacco leaves using the suspension cell alkalinization assay, and an N-terminal peptide sequence was obtained. This sequence allowed the identification of a full length tobacco cDNA indicating that the RALF gene encodes a 115 aa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Also consistent with this SST-localized and BS-specific developmental pattern are transcripts for the maize homologue of the secondary wall master regulator NST1 (GRMZM2G171395), three lignin biosynthetic genes and a laccase, suggesting that a burst of BS-specific wall strengthening occurs immediately before blade emergence ( Mitsuda et al , 2007 ; Berthet et al , 2011 ; Wang and Dixon, 2012 ). Also sharing this SST-localized, BS-specific pattern are three RALFs (rapid alkalinization factors) generally associated with growth inhibition ( Bedinger et al , 2010 ), and here perhaps terminating cell expansion for BS cells before the source transition.…”
Section: Resultsmentioning
confidence: 94%
“…Also consistent with this SST-localized and BS-specific developmental pattern are transcripts for the maize homologue of the secondary wall master regulator NST1 (GRMZM2G171395), three lignin biosynthetic genes and a laccase, suggesting that a burst of BS-specific wall strengthening occurs immediately before blade emergence ( Mitsuda et al , 2007 ; Berthet et al , 2011 ; Wang and Dixon, 2012 ). Also sharing this SST-localized, BS-specific pattern are three RALFs (rapid alkalinization factors) generally associated with growth inhibition ( Bedinger et al , 2010 ), and here perhaps terminating cell expansion for BS cells before the source transition.…”
Section: Resultsmentioning
confidence: 94%
“…Pearce et al [2] showed that mature peptides were almost 50 aa and contain four highly conserved cysteines in the C-terminus, which are essential for activation and are likely involved in disulfide bridges. The mature peptides also contain other conserved regions, such as the YISY motif near the N-terminus, a GASYY motif between the first and second conserved cysteines, and a PYXRGCS motif that contain the third conserved cysteine residue [3]. The YIXY motif is the key regulatory functional element required for targeting RALF to its putative receptor.…”
Section: Introductionmentioning
confidence: 99%
“… 16 In addition, RALF is a recently discovered family of plant peptide that plays a role in plant cell growth as will be described below. 17 …”
Section: Introductionmentioning
confidence: 99%